A rapid PCR ELISA for the detection of activated K-ras in colorectal cancer. Issue 5 (October 1995) - Ward, R L; Santiago, F; Hawkins, N J; Coomber, D; O'Connor, T; Todd, A V
Abstract : Aims —To develop a rapid PCR ELISA procedure for the detection of mutations in K- ras in a microtitre plate format, and to evaluate the assay for the detection of these mutations in human colorectal cancer. Methods —An enriched PCR method was used with labelled primers, and PCR product was captured on GCN4 coated immunoassay plates. Detection of biotinylated mutant product was performed by colorimetric assay with streptavidin-horseradish peroxidase. The assay was used to determine K- ras status in a series of 60 human colorectal neoplasms, together with paired normal colonic mucosa. Results from gel electrophoretic analysis were compared with ELISA results. Results —The assay proved reliable in detecting K- ras mutations in DNA extracted from both fresh and paraffin embedded colorectal tumours. ELISA results were comparable with results from gel electrophoresis. Mutations of K- ras were detected in 16 of 48 adenocarcinomas and five of 12 adenomas but no mutations were detected in normal mucosa. There was a highly significant difference (p<0·0005) between optical density values for carcinomas with mutant K- ras and their paired normal data. Adenomas did not show the clear distinction between positive and negative results seen with carcinomas. Conclusions —This assay provides a rapid and reliable means of detecting mutations in codon 12 of the K- ras oncogene. The single tube format colorimetric analysis in microtitre plates and clear discrimination between mutant and wild type genes makes the assay suitable for automation. The occurrence of intermediate results in the case of adenomas provides support for the hypothesis that mutations of K- ras occur early in the course of colorectal carcinogenesis.